Altered soil microbial community composition and function in two shrub-encroached marshes with different physicochemical gradients. (March 2019) - Ho, Janet; Chambers, Lisa G.
Abstract: Important wetland functions, including regulating soil carbon (C) storage and water quality, are linked to biogeochemical processes mediated by soil microbes. Vegetation shifts such as shrub encroachment may alter the soil microbial community and result in changes in important biogeochemical processes, although few studies have examined this in subtropical marshes. Here, we used in-situ litter decomposition experiments, quantitative polymerase chain reaction, and laboratory assays on soil respiration, extracellular enzyme activity, and denitrification potential to determine differences in C storage and nitrogen (N) cycling between willow-encroached and non-encroached plots in two subtropical marshes (Moccasin Island and Lake Apopka, FL, USA). In both regions, encroached (willow or adjacent marsh) and non-encroached plots had distinctively different microbial communities, which were correlated with soil temperature and nutrient content. Greater enzyme activity, denitrification, and CO2 production were observed in willow and/or adjacent marsh plots compared to control marsh plots at Moccasin Island. Conversely, lower enzyme activity, denitrification, and CO2 production were detected in willow and/or adjacent marsh plots compared to control marsh plots at Lake Apopka. Despite differences in the response of biogeochemical processes and microbial community structure in the two study regions, in-situ decomposition rates were halved in willow litter compared to herbaceous litter in both regions, which was correlated with greater recalcitrant lignin content in willow litter. Ultimately, greater short-term litter C storage was observed in both study regions, but soil N cycling changes differed by region, potentially due to unique site characteristics such as hydroperiod and nutrient availability. Highlights: Willow litter decomposed 50% slower than herbaceous (sawgrass and cattail) litter. Greater soil fungi and archaea detected in willow-encroached marshes. Nitrogen cycling differences were observed in two willow-encroached marshes. Marshes' varying hydroperiods and soil properties may have influenced nutrient cycling. Soil physiochemical properties influenced microbial composition and function.